Co-endemicity of loiasis and onchocerciasis in rain forest communities in southwestern Nigeria. - Olusola Ojurongbe; Akeem Abiodun Akindele; Monsuru Adebayo Adeleke; Matthew Oyebode Oyedeji; Samuel Adeyinka Adedokun; Josephine Folashade Ojo; Callistus Adewale Akinleye; Oloyede Samuel Bolaji; Olusegun Adelowo Adefioye; Oluwaseyi Adegboyega Adeyeba (Public Library of Science (PLoS), 2015)
Loiasis is currently receiving attention as a disease of public health importance because of the possibility of increased risk of developing neurologic serious adverse event following mass ivermectin treatment against onchocerciasis in individual co-infected with Onchocerca volvulus and Loa loa.Rapid assessment procedure for loiasis (RAPLOA) was conducted in 12 communities covering the 3 senatorial districts of Osun State, Nigeria. A total of 960 people were interviewed for history of eye worm using the WHO guidelines for rapid assessment. The survey confirmed the presence of loiasis in all the 12 communities with 4 in Osun East/Ife south senatorial district being at high risk with a prevalence of over 40%. Based on the RAPLOA results, communities within Osun East/Ife south senatorial district were selected for microfilaraemic assessment of L. loa and O. volvulus. A total of 1115 and 1091 individuals were screened for L. loa and O. volvulus microfilaria worms respectively. 160 (14.3%) had L. loa microfilaria detected in their blood with 8 (5.0%) individuals having L. loa loads above 8000 mf/ml. 166 (15.2%) subjects had O. volvulus microfilaria (range 4-504 mf/ml) detected in their skin snip. 30 (2.69%) subjects were co-infected with both L. loa and O. volvulus. There was a significant variation in the prevalence (2.1% to 33.3%) of onchocerciasis in the communities studied (p = 0.001). Five (41.7%) of the studied communities had a prevalence that is equal to or greater than 20%.Low prevalence of onchocerciasis and loiasis co-infection in this study suggests that loiasis may not pose a serious epidemiological threat to the continuous distribution and sustainability of ivermectin for the treatment of onchocerciasis. Evaluation of the interruption of onchocerciasis transmissions in this region using all the indicators set forth by WHO is therefore suggested.